Differentiating emissions targets for individual developed countries: economics and equity - Andy Reisinger (Kiel Institute for the World Economy (IfW), 2009)
A key challenge for a future climate change agreement is allocating emissions targets for individual developed countries that are perceived as equitable given differing national circumstances. Many economics-based frameworks for evaluating future targets use as a key criterion for individual country targets the notion that mitigation measures should result in similar costs (specifically, that the required mitigation actions relative to baseline emissions result in a similar percentage reduction of individual countries' GDP in the target year or period). Such an economic criterion provides a transparent and objective basis for comparison, but it does not necessarily mean that comparable targets for individual countries are also equitable. A set of thought experiments demonstrates that such an approach indeed does not reflect equity between countries. This is because future business-as-usual emissions, against which the costs of mitigation are assessed, depend on past policy choices and mitigation pathways. An approach that sets future emissions targets at a specific date based on comparable costs, without regard to past policy choices and commitments, would penalise countries that have taken early action and provides a disincentive for taking strong domestic mitigation actions in future. This analysis suggests that the choice of 'business-as-usual' emissions against which the future costs of mitigation are assessed needs to receive more attention if economic comparability is intended to also reflect equity of emissions targets over time.
Keywords: A13; F51; Q54; 330; Greenhouse gas mitigation; equity of emissions targets; comparability; economic impact; path-dependence; optimal policy design